Implementasi Ajaran Hatha Yoga Pada Gheraṇḍa Saṁhitā Dalam Kehidupan Praktis - I Made Sugata; Made G. Juniartha (Jurnal Penelitian Agama Hindu, 2022)
This research is a qualitative research that examines the text as well as the context or implementation of the teachings contained in the Gheraṇḍa Saṁhitā which is one of the main texts in learning yoga. The study of this text is important considering that yoga has become very popular in this century, but in its very practical form, it often forgets to study sources of knowledge in the form of the original text. By applying the Hermeneutic theory, the structural functional theory of the AGIL scheme and the theory of perception in examining the text and context, while the analysis is carried out using the verstehen method or understanding method. The results of the study indicate that the Gerandha Samhita book states that there are seven principles of yoga practice that must be practiced by practitioners / aspirin yoga, in order to achieve self-realization, including: (1) shatkarma, (2) asanas, (3) mudras, (4) pratyahara, (5) pranayama, (6) dhyana and (7) samādhi. Of the 7 (seven) forms of yoga exercises mentioned in the Gerandha Samhita text, they are classified as physical exercises such as shatkarma, asana, mudra and pranayama. All of these processes belong to Hatha Yoga. Through the practice of Hatha Yoga Gheraṇḍa Saṁhitā as the development of self-spirituality, namely knowing the secrets of the body as an evolutionary process in achieving the goal of moral, physical, mental and spiritual transformation.